2022
DOI: 10.3390/ijms23116028
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-Based Immunosensor for Dual-Mode Detection of Pathogenic F17–Positive Escherichia coli Strains

Abstract: Bacterial diseases cause tremendous economic losses due to high morbidity and mortality in livestock animals. F17A protein, the major subunit of F17 fimbriae, is one of the most prevalent and crucial virulence factors among the pathogenic Escherichia coli (E. coli) isolated from diarrheic and septicemic animals of various species. Purification and detection of this protein is regarded as an interesting field of investigation due to its important role as a therapeutic target, such as vaccines, and as a diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The rapid spread of sheep diseases has led to an increase in the culling of sheep and losses to breeding farms. Escherichia coli infections are a major threat to young animals and can be fatal in severe cases [ 51 , 52 ]. Therefore, the breeding of high quality disease-resistant sheep is an important issue, and the use of key genes or candidate sites that influence the occurrence of sheep diseases can improve the economic benefits of breeding enterprises and promote the healthy development of the sheep industry.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid spread of sheep diseases has led to an increase in the culling of sheep and losses to breeding farms. Escherichia coli infections are a major threat to young animals and can be fatal in severe cases [ 51 , 52 ]. Therefore, the breeding of high quality disease-resistant sheep is an important issue, and the use of key genes or candidate sites that influence the occurrence of sheep diseases can improve the economic benefits of breeding enterprises and promote the healthy development of the sheep industry.…”
Section: Discussionmentioning
confidence: 99%
“…Two microplates were coated overnight at 4 • C with 100 µL per well of each of the purified nanobodies diluted in PBS to a final concentration of 10 µg/mL. Post blocking with 5% skimmed milk in PBS for 2 h at RT, different concentrations (10 4 to 10 9 cells diluted in PBS buffer) of the E. coli F17 strain [23] and the control strain BL-21(DE3) were added and incubated for 1 h at 37 • C. A rabbit anti-F17A polyclonal antibody [12] diluted to 1/1000 was applied for 1 h at 37 • C. An anti-rabbit-HRP conjugated antibody (Invitrogen, Carlsbad, CA, USA) diluted to 1/5000 in PBS was used for detection. Three washes with PBS buffer were performed after each incubation.…”
Section: Vhh Binding By Cell-elisamentioning
confidence: 99%
“…As a result, researchers have suggested that this approach can reduce antibiotic use and mortality rates [11]. To develop biosensors for pathogenic bacteria, various signal transmission techniques have been investigated, including electrochemiluminescence, piezoelectric quartz crystal microbalance, and electrochemical approaches [12].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, F5 and F41 fimbriae have been recognized as the predominant pathogenic 2 of 11 factors in diarrheal ETEC, affecting different domestic animals [8,9]. In contrast, F17 fimbriae are associated with diarrhea and septicemia, commonly found in ETEC strains from ruminants [10]. Furthermore, recent epidemiological data have highlighted significant shifts in the prevalence of fimbrial types associated with calf diarrhea, shown by a decline in F5 and F41 fimbriae, while the emergence of F17 fimbriae was observed as the most common fimbriae in calf ETEC infection [11,12].…”
Section: Introductionmentioning
confidence: 99%